Tanda Tangan Elektronik pada Transaksi Jual Beli Online: Suatu Kajian Hukum Keamanan Data Konsumen di Indonesia - Hari Sutra Disemadi; Denny Prasetyo (Wajah Hukum, 2021)
This research will discuss and examine the importance of readiness for comprehensive regulations that function to strictly regulate the protection of personal data in using electronic signatures used in online buying and selling transactions. This research is legal research prepared using normative legal research methods. This research shows that the electronic signature in online buying and selling transactions is a legal term derived from a digital signature that functions to authenticate and verify a person's data that makes it electronically or online as a digital form of user identity, as well as proof of approval of an agreement on the transaction online as a form of prevention against cyber crime. Electronic signatures need to be considered where the government can prioritize ratifying this regulation to provide security guarantees for the protection of personal data when the owner of the electronic signature uses it to verify and validate an agreement contract in online transactions. The protection in question is a rule which regulates data sovereignty, rights, and obligations of the parties, along with criminal and civil sanctions to prevent misuse of personal data.